Analysis of The Implementation of Sharia Strategy Management at BMT Maslahah - Toha, Mohamad; Ulfa, Elly; Yanti Sandra Dewi, Novi (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2021)
Strategic management is a determinant of employee performance in the long term with the level of managerial decisions and actions. It includes environmental observation, strategy formulation, strategy implementation, evaluation and control. The research was conducted to analyze Sharia Strategic Management (MSS) at BMT Maslahah. It uses qualitative research methods, while data collection through interview techniques and documentation techniques. After the research was conducted, it was found that the strategic management process used by BMT Maslahah would be updated according to the needs and long-term development of the company. As for the strategy formulation, it is done by gathering all the members who will later be adjusted to the suggestions and the results of the joint discussion. The implementation of the strategy is adjusted to the existing mission at BMT Maslahah, such as managing cooperatives according to the identity of the students and also implementing the sharia system using the salaf book standards as well as in accordance with the fatwas of the National Sharia Council (DSN). It is stated that the BMT Maslahah in its implementation has implemented sharia principles which are marked by the implementation of four aspects differentiating it from conventional strategic management, including aspects of tawhid, orientation, motivation and sharia strategy.